2016
DOI: 10.1371/journal.pone.0167556
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Heterogeneity of Multiple Sclerosis Prevalence in France

Abstract: IntroductionGeographical variation in the prevalence of multiple sclerosis (MS) is controversial. Heterogeneity is important to acknowledge to adapt the provision of care within the healthcare system. We aimed to investigate differences in prevalence of MS in departments in the French territory.MethodsWe estimated MS prevalence on October 31, 2004 in 21 administrative departments in France (22% of the metropolitan departments) by using multiple data sources: the main French health insurance systems, neurologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Moreover, when compared to other western regions, the prevalence in Saudi Arabia is considered low. The prevalence in other western countries was reported as high as 98.4/100,000, 106.6/ 100,000, 170.9/100,000 and 179.9/100,000 in central Italy, Italy, France, Columbia and Canada respectively [19][20][21][22]. The variation in the prevalence could be related to many factors, for example genetic variation, certain environmental factors, role of ethnicity and other variations related to methodologies followed in the different studies; however, the increased prevalence is consistently reported across the different studies conducted globally and in neighboring countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, when compared to other western regions, the prevalence in Saudi Arabia is considered low. The prevalence in other western countries was reported as high as 98.4/100,000, 106.6/ 100,000, 170.9/100,000 and 179.9/100,000 in central Italy, Italy, France, Columbia and Canada respectively [19][20][21][22]. The variation in the prevalence could be related to many factors, for example genetic variation, certain environmental factors, role of ethnicity and other variations related to methodologies followed in the different studies; however, the increased prevalence is consistently reported across the different studies conducted globally and in neighboring countries.…”
Section: Discussionmentioning
confidence: 99%
“…20 King Fahad Specialist Hospital, Dammam, Qassim, Saudi Arabia. 21 King Abdullah Bin Abdulaziz University Hospital, Riyadh, Saudi Arabia. 22 Itkan Health Consulting, Riyadh, Saudi Arabia.…”
Section: Fundingmentioning
confidence: 99%
“…The prevalence in other western countries was reported as high as 98.4/100,000, 106.6/100,000, 170.9/100,000 and 179.9/100,000 in central Italy, Italy, France, Columbia and Canada respectively. (19)(20)(21)(22) The variation in the prevalence could be related to many factors, for example genetic variation, certain environmental factors, role of ethnicity and other variations related to methodologies followed in the different studies; however, the increased prevalence is consistently reported across the different studies conducted globally and in neighboring countries. The female to male ratio in our study was 2:1 nearly similar to the two recent studies conducted in the MENA region, R. Alroughani et al and Hamdy et.…”
Section: Discussionmentioning
confidence: 99%
“…This chronic disease is one of the most common causes of disability in young populations ( 2 ). In Europe, prevalence of MS is rising ( 3 ); however, geographical variations may be observed ( 4 , 5 ). It remains unclear whether this heterogeneity can be attributed exclusively to genetic and environmental factors, since access to healthcare and insurance policies varies across countries and may influence the results of prevalence studies performed on this continent.…”
Section: Introductionmentioning
confidence: 99%